Key Indicators for Evaluating the Energy Efficiency Improvement of the Renovated Building Facades - Dimevska, Liljana; Knezevic, Milos; Cvetkovska, Meri; Trombeva-Gavriloska, Ana; Mihajlovska, Teodora (Springer Nature Switzerland, 2023)
Adopting the circular economy (CE) principles in building sector can reduce the quantity of materials used for the renovation of existing buildings, improve their energy performance and sustainability and minimize harmful emissions embodied in building materials. The main key indicators for energy performance evaluation of buildings, related to CE principles are: transmission losses, heating and electricity energy consumption, greenhouse gas emissions (GHGs), thermal comfort and financial costs for building maintenance. The building stock from the sixties and seventies is still in use, but from the aspect of energy efficiency, it shows a low level. From that reason, all these buildings have to be renovated. The effects of the renovation can be followed by the values of the key indicators. A simulation of a renovated scenario of an existing building was carried out and the results are presented in this paper. The analyzed building was built only in nature concrete without any facade thermal insulation. One of the renovation conditions was the appearance of the building should not be changed. An aerogel thermal plaster, which is nanomaterial with high thermal properties, was applied on the building facade. The results shows that the energy performance of the building is significantly improved in terms of reducing the heating energy consumption by 65%, electrical energy consumption by 40%, CO2 emissions by 55%, PM10 particles by 46%, and the financial costs by 49%. According to the key indicators, it is found out that the renovation with appropriate material can significantly improve the building functionality.